THE URGENCY OF INTERNALIZATION OF WOMEN'S PROBLEMS AND EXPERIENCES IN NATURAL RESOURCES REGULATION IN SOUTH KALIMANTAN - Erlina Erlina; Lena Hanifah; Elma Fitria; Giovanni Akmal Firdausy; Zhafirah Zahra (Scholar Center, 2021)
Women and nature are often articulated as two things that are very close and near . Environmental problems that occur today are not gender-neutral because when natural damage occurs, women are the parties most at risk of being affected. Exploitation and conflict of natural resources affect women's welfare. On the other hand, women still experience various obstacles in fighting for and defending their environment and life, women's access and control over natural resources are still minimal, while women are also almost not involved in decision making, face stigmatization, and so on. This study uses the research method of socio-legal research by using an interdisciplinary approach between aspects of normative research and a sociological approach. The results showed that women's groups were not involved in the formation of regulations in the field of natural resources in South Kalimantan and the existing arrangements had not specifically accommodated women's problems, needs, knowledge, and experiences.